Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/infdis/jiw077
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Pharmacology Approach to Predicting Outcomes of Preexposure Prophylaxis Against HIV in Men and Women Using Tenofovir Disoproxil Fumarate With or Without Emtricitabine

Abstract: This model is predictive of recent PrEP trial results in which 2-3 doses/week was 75%-90% effective in men but ineffective in women. These data provide a novel approach for future PrEP investigations that can optimize clinical trial dosing strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
309
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(328 citation statements)
references
References 39 publications
14
309
3
2
Order By: Relevance
“…Pharmacokinetic data suggest that individuals should take several daily doses upon PrEP initiation to achieve steady-state tenofovir levels in blood and longer in tissue compartments, ranging from a few days for men who have sex with men to 1–3 weeks in women(18, 19). Additionally, risk for HIV acquisition may be difficult to anticipate(20).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic data suggest that individuals should take several daily doses upon PrEP initiation to achieve steady-state tenofovir levels in blood and longer in tissue compartments, ranging from a few days for men who have sex with men to 1–3 weeks in women(18, 19). Additionally, risk for HIV acquisition may be difficult to anticipate(20).…”
Section: Discussionmentioning
confidence: 99%
“…TFV can be detected in plasma for about one week after oral dosing, indicating longer-term systemic availability of TFV than has been seen for gel-based PrEP but lower concentrations in vaginal tissue than gel-based dosing (32,38). Pharmacokinetic studies of oral PrEP have shown that TFV-DP has more difficulty reaching protective concentrations in the female genital tract than in colorectal tissue, and higher levels of adherence (about 6–7 doses/week) are thought to be required to provide effective HIV prevention for people having vaginal exposure to HIV (38,39 ■ ). Results from the Partners PrEP Study, VOICE, and FEM-PrEP have shown that oral FTC/TDF and TDF are efficacious with high adherence levels, but oral PrEP is not protective for women with lower adherence to the dosing regimen (7,23 ■ ,24).…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Tenofovir plasma parameters are consistent with the literature (22, 23), which generally describes tenofovir disposition as a two-compartment model. For tissue parameters, no direct comparators are available in the literature, though estimates are similar in magnitude to those of Cottrell et al(21) Standard diagnostic plots are included in the Supplement.…”
Section: Methodsmentioning
confidence: 89%
“…This “true” model was built by fitting data from the terminal tissue and plasma compartments from the Patterson et al study (20) and plasma data from Cottrell et al study. (21) This model consisted of a four compartment model, as seen in Figure 1. A standard two-compartment model described the plasma concentrations, with an additional compartment to describe drug transfer from plasma to tissue and a compartment to describe drug transfer from the rectal tissue to a transit compartment (tissue compartment 2) then back to the plasma (central compartment).…”
Section: Methodsmentioning
confidence: 99%